High-toughness wear-resistant badminton composite material and preparation method thereof
By adopting a multi-layer structure of high-tough wear-resistant badminton composite material, the problems of poor durability and insufficient wear resistance of existing badminton materials are solved, and the high wear resistance and toughness of the material is achieved, which is suitable for applications in high-strength training and event scenarios.
Patent Information
- Application Number
- CN202411865752.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
The existing badminton materials and preparation processes have problems such as poor durability, insufficient wear resistance and low production efficiency, which is difficult to meet the needs of high-intensity training and event scenarios.
Using a high-toughness and wear-resistant badminton composite material, including ultra-high molecular weight polyethylene, ceramic micropowder, silane coupling agent, polytetrafluoroethylene micropowder, modified thermoplastic elastomer, polyurethane, nano calcium carbonate, glass fiber reinforced nylon and other components, a multi-layer structure is constructed to improve material performance through fine material formulation and preparation process.
It achieves high wear resistance and toughness of the material, extends the service life of the badminton, improves flight stability and batting feedback, and is suitable for applications in multiple scenarios.
Smart Images

Figure SMS_6 
Figure SMS_7 
Figure SMS_21
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a high-toughness wear-resistant badminton composite material and a preparation method thereof. Background Art
[0002] Badminton is a highly popular sport, and the performance of its core component, the shuttlecock, is directly related to the sports experience and competitive level. Traditional badminton materials and preparation processes have gradually exposed many drawbacks that are difficult to ignore in long-term practical applications, and they are in urgent need of innovation and optimization.
[0003] In terms of materials, common badmintons in the past were mostly made of natural feathers with cork heads. Although natural feathers give badmintons good flight stability and batting feel, their natural properties make them extremely durable. Natural feathers are easily affected by environmental factors such as humidity and temperature. In a high humidity environment, they easily absorb water, become heavy and soft, and their flight trajectory is disordered. In addition, feathers are easy to break and fall off when hitting the ball, which seriously shortens the service life. Frequent replacement of badminton increases the cost of use and resource consumption, limiting the efficient application of badminton in long-term high-intensity training and competition scenarios. The cork head has limited strength and insufficient impact resistance. It is easy to dent and deform after multiple hits, affecting the overall flight stability and batting feedback.
[0004] With the development of material science, some synthetic materials are used in badminton manufacturing, but the existing synthetic material solutions also have shortcomings. Some balls made of conventional plastic materials have poor wear resistance. During the frequent high-speed friction and collision with the racket net line and the venue, the surface wears quickly, resulting in abnormally increased flight resistance and unstable flight distance, which affects the player's prediction and control. At the same time, the lack of toughness makes it difficult to effectively buffer and disperse the impact force at the moment of hitting the ball, and it is easy to crack or even break, and cannot withstand repeated hitting in professional training and competitions.
[0005] From the perspective of preparation methods, traditional natural feather badminton is largely handmade, relying on the experience and skills of craftsmen, with extremely low production efficiency, and it is difficult to mass-produce to meet the growing market demand. In addition, the quality consistency is difficult to control in the process of manually pasting feathers and assembling the ball head. The slight differences between each badminton may cause fluctuations in flight and hitting performance, making it difficult to ensure a fair competitive environment in high-standard competitions.
[0006] Although the preparation process of synthetic badminton has the advantage of process-based operation, most existing processes lack fine and coordinated control of materials. For example, in the blending process, the components are simply mechanically mixed without fully considering the interface compatibility and microstructural interaction of different materials, resulting in phase separation, agglomeration and other undesirable phenomena inside the material, which greatly reduces the overall performance of the product. During injection molding, the parameters are roughly set, which cannot ensure that each layer of material fills the mold evenly and is tightly combined, resulting in interlayer peeling and stratification, affecting the mechanical properties and durability of the product. It is impossible to take into account the balanced improvement of multi-dimensional key performances such as wear resistance, toughness, and stability, and it is difficult to produce high-quality badminton that fits professional sports and mass fitness scenarios. The patent of this invention aims to overcome the above-mentioned drawbacks, innovate material formulas and preparation processes, and open up new paths to improve the performance of badminton. Summary of the invention
[0007] In view of the deficiencies of the prior art, the technical solution adopted by the present invention to solve the technical problems is: a high-toughness wear-resistant badminton composite material, comprising: 55-65 parts of ultra-high molecular weight polyethylene, 20-30 parts of ceramic powder, 2-3 parts of silane coupling agent, 3-5 parts of polytetrafluoroethylene powder, 45-55 parts of modified thermoplastic elastomer, 25-35 parts of polyurethane, 10-15 parts of nano calcium carbonate, 4-6 parts of dioctyl phthalate, 1-2 parts of hindered phenol antioxidant, 50-60 parts of glass fiber reinforced nylon, 20-30 parts of glass fiber, 10-15 parts of polyoxymethylene and 1-2 parts of zinc stearate, wherein the preparation method of the modified thermoplastic elastomer is as follows: Step A1: weighing the thermoplastic elastomer and polybutylene terephthalate in a mass ratio of 80:20, placing them in a vacuum oven, and drying them at 80° C. for 4-6 hours; Step A2: setting the temperature to 180° C., firstly adding the dried thermoplastic elastomer into a vacuum oven through a co-rotating twin-screw extruder, and after the dried thermoplastic elastomer is initially melted, adding polybutylene terephthalate, blending through a screw extruder, and then extruding through a die head, cooling in a water tank, drawing and pelletizing, to obtain a primary modified thermoplastic elastomer; This step is mainly the physical blending process of thermoplastic elastomer (TPE) and polybutylene terephthalate (PBT) under heating and screw shearing. In the co-rotating twin-screw extruder, first put the TPE particles dried in a vacuum oven at 80℃ for 4-6 hours into zone 1 (the temperature is set to 180℃). As the screw rotates at 300rpm, the TPE particles gradually melt under the heat, forming a viscous flow state, and the molecular chains begin to stretch and activate. At this time, the PBT particles that have also been dried are added from the side feed port. The material continues to move forward with the screw, passing through the higher temperature areas of zone 2 (200℃), zone 3 (210℃), and zone 4 (220℃) in turn. Under the gradually increasing temperature and the strong shearing, stirring, and kneading of the screw, the TPE molecular chains and the PBT molecular chains interweave, entangle, and diffuse with each other, achieving a tight and uniform physical mixing. Finally, after extrusion, cooling and pelletizing, a modified thermoplastic elastomer (TPE-PBT) is obtained. This product has both the elasticity of TPE and the rigidity of PBT, laying a solid structural foundation for subsequent further modification. Step A3: Add nano-silicon dioxide to the primary modified thermoplastic elastomer, disperse it using an ultrasonic dispersing device to obtain a uniform suspension, and then dropwise add , stirring after oil bath; Step A4: The primary modified thermoplastic elastomer and nano-silicon dioxide are weighed at a mass ratio of 95:5, and then placed in a high-speed mixer for premixing, and then placed in a twin-screw extruder. After cooling and pelletizing, a secondary modified thermoplastic elastomer is obtained. The specific reaction formula is as follows: ; Step A5: Taking the secondary modified thermoplastic elastomer as a matrix, diisopropylbenzene oxide and triallyl isocyanurate are weighed in a mass ratio of 0.5%:1%, and the secondary modified thermoplastic elastomer is first placed in a high-speed mixer, and diisopropylbenzene oxide and triallyl isocyanurate are added in sequence during the stirring process to obtain a mixed material, and the mixed material is put into an internal mixer to obtain a modified thermoplastic elastomer. The specific reaction formula is as follows: ; .
[0008] Preferably, the molecular weight of the ultra-high molecular weight polyethylene is greater than 1.5 million, the ceramic micropowder is a mixture of aluminum oxide and zirconium oxide, the silane coupling agent has a methoxy group at one end and an epoxy group at the other end, the polytetrafluoroethylene is a high molecular polymer prepared by polymerization of tetrafluoroethylene as a monomer, the polyurethane is a high molecular polymer generated by the reaction of polyols and isocyanates, the particle size of the nano calcium carbonate is between 1-100 nm, and the hindered phenol antioxidant is antioxidant 3114.
[0009] Preferably, in step A2, the vacuum oven is divided into four zones, the temperature of zone 1 is set to 180°C, the screw speed is set to 300r / min, and during the blending process of the screw extruder, the material moves to subsequent zones, the temperature of zone 2 is 200°C, the temperature of zone 3 is 210°C, and the temperature of zone 4 is 220°C.
[0010] Preferably, in step A3, the particle size of nano-silicon dioxide is 20-50 nm, and it is dispersed with anhydrous ethanol solution at a mass ratio of 10:1, the dispersing power of the ultrasonic dispersing equipment is 400W-600W, the dispersing time is 30-45min, and the silane coupling agent added is The silica is KH-550, and the silane coupling agent accounts for 3% to 5% of the mass of the silica. The oil bath temperature is 60° C. to 70° C., and the stirring speed is 300 to 400 r / min.
[0011] Preferably, in step A4, the premixing time is 15 to 20 minutes, the premixing speed is 600-800 r / min, the twin-screw extruder is divided into five zones, the temperature of zone one is 190°C, the temperature of zone two is 210°C, the temperature of zone three is 220°C, the temperature of zone four is 230°C, the temperature of zone five is 230°C, and the screw speed is 400 r / min.
[0012] Preferably, in step A5, the secondary modified thermoplastic elastomer is placed in a high-speed mixer at a rotation speed of 200-300 r / min and a stirring time of 10-15 min. The internal mixer is preheated to 170° C. before the material enters. After the material enters, the rotation speed is 30-40 r / min and the internal mixing time is 10-15 min. The modified thermoplastic elastomer obtained has a three-dimensional cross-linked network structure.
[0013] A method for preparing a high-toughness wear-resistant badminton composite material comprises the following steps: Step B1: placing ultra-high molecular weight polyethylene particles in a vacuum oven to dry, then adding ceramic micropowder, stirring at high speed, adding silane coupling agent, extruding, cooling in a water tank, drying, and pelletizing to obtain an outer wear-resistant layer material; Step B2: respectively putting the modified thermoplastic elastomer, polyurethane, nano calcium carbonate, dioctyl phthalate, and hindered phenol antioxidant into a mixer, stirring and heating to obtain a middle toughening layer material; Step B3: placing the glass fiber in an oven to remove impurities, then soaking it in a diluted silane coupling agent solution and drying it, adding glass fiber reinforced nylon, treated glass fiber, polyoxymethylene and zinc stearate to a mixer in sequence for premixing, and then extruding it to obtain an inner support layer material; Step B4: injecting the outer wear-resistant layer material, the middle toughening layer material and the inner support layer material into the mold through an injection molding machine, and after cooling and demolding, obtaining a high-toughness wear-resistant badminton composite material.
[0014] Preferably, in step B1, the ultra-high molecular weight polyethylene particles are dried at 80-90°C for 4-6 hours, the ceramic powder is mixed with alumina and zirconium oxide in a mass ratio of 2:1, and dried at 100-110°C for 3-5 hours, and the amount of silane coupling agent added is 2% to 3% of the mass of the ceramic powder.
[0015] Preferably, in step B2, the speed of the stirrer is 800-1000 r / min, the time is 20-30 min, and the heating temperature is 80-90°C.
[0016] Preferably, in step B3, the impurity removal temperature of the glass fiber is 120-130° C., the impurity removal time is 2-3 hours, and the silane coupling agent dilution solution is prepared by mixing the silane coupling agent and water in a mass ratio of 1:10.
[0017] The beneficial effects of the present invention are as follows: 1. Carefully construct a wear-resistant system on the outer layer of the material. Ultra-high molecular weight polyethylene is used as the matrix, which has good flexibility and basic wear-resistant properties. It is evenly dispersed in the material with high-hardness ceramic micropowder (coordinated by alumina and zirconia), just like putting a solid "armor" on the material. The silane coupling agent is like a "bridge", tightly connecting the inorganic ceramic micropowder and the organic matrix, ensuring that the outer layer structure is stable under frequent friction and impact conditions, and the wear-resistant particles are not easy to fall off, effectively resisting external wear. Polytetrafluoroethylene micropowder further exerts its self-lubricating advantages, reduces the friction coefficient, and reduces the friction loss caused by contact with the racket, air, etc., greatly extending the service life of the badminton, so that it can still maintain a good appearance and flight performance after multiple hits and flights.
[0018] 2. The core lies in the middle toughening layer composed of modified thermoplastic elastomer and polyurethane. The modified thermoplastic elastomer has undergone three fine modifications, starting with the introduction of rigid chain segment blending, and then fused with polybutylene terephthalate to optimize the molecular chain structure and enhance the initial support; then it is reinforced by nano-silicon dioxide filling, and the internal microstructure is strengthened and the impact energy is dissipated by the nano effect; finally, it is dynamically cross-linked to form a three-dimensional network to stabilize the overall structure. The unique soft and hard segment structure of polyurethane is synergistic, and the two are interwoven into an interpenetrating network, which can efficiently absorb and disperse the impact force of the ball at the moment of force, and inhibit the initiation and expansion of cracks through multiple microscopic mechanisms, giving the material excellent elastic recovery ability, ensuring that the badminton rebounds quickly after impact and does not deform, and maintains a stable flight posture.
[0019] 3. The inner layer uses glass fiber reinforced nylon combined with glass fiber to construct a strong support structure. Glass fiber bears the main load with its high strength and high modulus characteristics, restrains the development of cracks, and enhances the overall rigidity. After pre-treatment with silane coupling agent, it is closely combined with the matrix to ensure uniform and efficient force transmission. Polyoxymethylene assists in optimizing wear resistance and support. The various components work together to make the inner layer provide a solid "skeleton" for the badminton and maintain a stable shape. At the same time, hindered phenolic antioxidants escort the whole process, inhibit the oxidation and aging of the material, and protect the stability of the internal chemical structure, ensuring that the material performance does not decay during long-term storage and frequent use, and the mechanical and physical properties are always reliable. The layers are closely combined and complement each other, achieving excellence and stability in the overall performance of the product from microscopic molecules to macroscopic molecules, which meets the complex force and changeable use environment requirements of badminton.
[0020] 4. From raw material pretreatment, co-mixing and extrusion of each layer of materials to injection molding, each link is equipped with fine parameter control. The moisture content of raw material drying is controlled to ensure processing quality; co-mixing and extrusion sets multiple temperature and screw speed according to the material characteristics to ensure that the components are evenly dispersed and fully reacted and fused, just like the temperature zones of the twin-screw extruder work together to "carve" the material properties; injection molding is finely adjusted according to the layer sequence and the mold to achieve close fit and seamless connection of each layer. The whole process is precise and standardized, with strong repeatability and stability, which not only ensures that the performance of each batch of products is highly consistent, but also is easy to mass produce, laying a solid foundation for the commercial promotion of products and efficiently meeting the market demand for high-quality badminton composite materials. DETAILED DESCRIPTION
[0021] The present invention is further described in detail below in conjunction with specific embodiments. The embodiments of the present invention are provided for the purpose of illustration and description, and are not intended to be exhaustive or to limit the present invention to the disclosed forms. Many modifications and variations will be apparent to those of ordinary skill in the art. The embodiments are selected and described to better illustrate the principles and practical applications of the present invention, and to enable those of ordinary skill in the art to understand the present invention and thereby design various embodiments with various modifications suitable for specific uses.
[0022] Embodiment 1: Experimental Group Material formula: 65 parts of ultra-high molecular weight polyethylene, ceramic powder (Al 2 O 3 :ZrO 2 =2:1) 30 parts, silane coupling agent 3 parts, polytetrafluoroethylene powder 5 parts, modified thermoplastic elastomer 55 parts, polyurethane 35 parts, nano calcium carbonate 15 parts, dioctyl phthalate 6 parts, hindered phenol antioxidant (antioxidant 3114) 2 parts, glass fiber reinforced nylon 60 parts, glass fiber 30 parts, polyoxymethylene 15 parts, zinc stearate 2 parts. The modified thermoplastic elastomer is prepared strictly according to the following steps: Step A1: Thermoplastic elastomer and polybutylene terephthalate were weighed in a ratio of 80:20, placed in a vacuum oven, and dried at 80° C. for 6 hours.
[0023] Step A2: Set the temperature of the first zone of the co-rotating twin-screw extruder to 180°C, add the dry thermoplastic elastomer first, and after initial melting (screw speed 300r / min), add polybutylene terephthalate, and the material moves forward with the rotation of the screw. The temperature of the second zone rises to 200°C, the temperature of the third zone to 210°C, and the temperature of the fourth zone to 220°C. After the blending is completed, it is extruded through the die head, cooled in a water tank, drawn into strips and pelletized to obtain a primary modified thermoplastic elastomer.
[0024] Step A3: Select nano-silica with a particle size of 20-50 nm, disperse it with anhydrous ethanol solution in an ultrasonic dispersion device at a mass ratio of 10:1, disperse it for 45 minutes to form a uniform suspension, add KH-550 accounting for 5% of the mass of the nano-silica, and stir it at 400 r / min in a 70°C oil bath.
[0025] Step A4: weigh the primary modified thermoplastic elastomer and nano-silicon dioxide at a mass ratio of 95:5, put them into a high-speed mixer for premixing at 800 r / min for 20 minutes, put them into a twin-screw extruder (zone 1 temperature 190°C, zone 2 temperature 210°C, zone 3 temperature 220°C, zone 4 temperature 230°C, zone 5 temperature 230°C, screw speed 400 r / min), cool and pelletize to obtain a secondary modified thermoplastic elastomer.
[0026] Step A5: With the secondary modified thermoplastic elastomer as the matrix, weigh 0.5% of diisopropylbenzene peroxide and 1% of triallyl isocyanurate in a mass ratio, first place the secondary modified thermoplastic elastomer in a high-speed mixer (speed 300r / min), add the above two in sequence during stirring for 15 minutes to obtain a mixed material, put the mixed material into a mixer preheated to 170°C (after the material enters, the speed is 40r / min), and mix for 15 minutes to obtain a three-dimensional cross-linked network structure modified thermoplastic elastomer.
[0027] Preparation method: Step B1: The ultra-high molecular weight polyethylene particles were placed in a vacuum oven and dried at 90°C for 6 hours, and then ceramic micropowder (Al 2 O 3 :ZrO 2 =2:1), stirred with a high-speed mixer at 1000r / min, added with silane coupling agent (3% of the mass of ceramic micropowder), extruded by a twin-screw extruder (the temperature of each area is set according to the process to ensure uniform plasticization and extrusion of the material), cooled in a water tank, blown dry, and pelletized to obtain the outer wear-resistant layer material.
[0028] Step B2: respectively put the modified thermoplastic elastomer, polyurethane, nano calcium carbonate, dioctyl phthalate and hindered phenol antioxidant into a mixer, stir at 1000 r / min and heat to 90° C., stir for 30 minutes to obtain a middle toughening layer material.
[0029] Step B3: Place the glass fiber in a 130°C oven to remove impurities for 3 hours, then soak it in a diluted silane coupling agent solution (silane coupling agent and water are prepared in a mass ratio of 1:10) and dry it, add glass fiber reinforced nylon, treated glass fiber, polyoxymethylene and zinc stearate to a mixer for premixing (premixing speed 800r / min, premixing for 15 minutes), and then extrude it through a twin-screw extruder (the temperature of each area is set according to the inner layer process) to obtain the inner support layer material.
[0030] Step B4: Inject the outer wear-resistant layer material, the middle toughening layer material and the inner support layer material into the mold through an injection molding machine (the injection molding parameters are carefully set according to the mold characteristics and material flow requirements, including injection pressure, speed, holding time, etc.), and after cooling and demolding, a high-toughness wear-resistant badminton composite material is obtained.
[0031] Test method: According to the national standard "Measurement Method for Wear Resistance of Plastics", the Taber wear tester was used for testing. Before the test, the prepared composite material was processed into a circular specimen with a diameter of 50mm and a thickness of 5mm, and the surface of the specimen was cleaned and polished to ensure that the surface was flat, flawless, and isotropic. During the test, a 5N weight was fixed on the surface of the specimen, and an H-18 grinding wheel was selected as the friction medium. The speed of the testing machine was set to 7200r / min, and the grinding wheel was allowed to continuously contact and rub with the surface of the specimen for 1000 revolutions. After completing the friction test, an electronic balance with an accuracy of 0.0001g was used to weigh the mass of the specimen before and after friction, and the mass loss rate was calculated by the mass difference to evaluate the wear resistance of the material. The average value was taken after 5 repeated tests to ensure data reliability and accuracy.
[0032] Test data: The average mass loss rate is 0.07%, the surface wear is slight, only very fine and shallow scratches are visible, and microscopic observation shows that the structural integrity of the material in the worn area remains good, and there is no obvious shedding or displacement of the reinforcing fibers and wear-resistant particles, and the overall wear resistance of the material is excellent.
[0033] Control group 1 Material formula: 55 parts of ultra-high molecular weight polyethylene, ceramic powder (Al 2 O 3 :ZrO 2=2:1) 20 parts, silane coupling agent 2 parts, polytetrafluoroethylene powder 3 parts, modified thermoplastic elastomer 45 parts, polyurethane 25 parts, nano calcium carbonate 10 parts, dioctyl phthalate 4 parts, hindered phenol antioxidant (antioxidant 3114) 1 part, glass fiber reinforced nylon 50 parts, glass fiber 20 parts, polyoxymethylene 10 parts, zinc stearate 1 part. The modified thermoplastic elastomer is prepared according to the corresponding minimum proportion and standard steps (the parameters of steps A1-A5 are performed at the lowest setting, such as A1 drying for 4 hours; A2 each temperature zone of the twin-screw extruder is set at the lowest temperature, the screw speed is 300r / min; A3 nano silicon dioxide dispersion power is 400W, dispersion for 30min, etc.).
[0034] Preparation method: The preparation steps are the same as those of the experimental group, but only the ingredients are prepared according to the minimum number of ingredients. The parameters of each equipment are set according to the lower limit of the process. The ultra-high molecular weight polyethylene in B1 is dried at 80℃ for 4 hours, and the ceramic micropowder is dried at 100℃ for 3 hours; B2 mixer is 800r / min, heated to 80℃, and stirred for 20 minutes; B3 glass fiber is decontaminated at 120℃ for 2 hours, and the lower limits of subsequent premixing and extrusion parameters are set.
[0035] Test method: The same test method as the experimental group was used to prepare samples of the same specifications. The mass loss rate was measured after rubbing for 1000 revolutions at a speed of 7200r / min in the same Taber wear tester, loaded with a 5N weight, an H-18 grinding wheel, and repeated 5 times.
[0036] Test data: The average mass loss rate is 0.18%, the surface scratches are significantly increased and deepened, some ceramic powders can be seen falling off under the microscopic view, there are tiny cracks at the interface between the matrix and the wear-resistant phase, and the wear resistance of the material is significantly reduced compared with the experimental group.
[0037] Control group 2 Material formula: 65 parts of ultra-high molecular weight polyethylene, ceramic powder (Al 2 O 3 :ZrO 2 =2:1) 20 parts, silane coupling agent 3 parts, polytetrafluoroethylene powder 5 parts, modified thermoplastic elastomer 55 parts, polyurethane 35 parts, nano calcium carbonate 15 parts, dioctyl phthalate 6 parts, hindered phenol antioxidant (antioxidant 3114) 2 parts, glass fiber reinforced nylon 60 parts, glass fiber 30 parts, polyoxymethylene 15 parts, zinc stearate 2 parts. That is, keep the other components at the maximum value of the interval or the selected value of the experimental group, only adjust the ceramic powder to the minimum value of 20 parts, and the modified thermoplastic elastomer is prepared according to the high standard steps of the experimental group.
[0038] Preparation method: Similar to the preparation process of the experimental group, the ingredients are adjusted according to the corresponding number of ingredients, and the parameters of each process link are implemented according to the high standards of the experimental group. The ultra-high molecular weight polyethylene in B1 is dried at 90℃ for 6 hours, and the ceramic micropowder is dried at 110℃ for 5 hours; B2 mixer 1000r / min, heated at 90℃, stirred for 30 minutes; B3 glass fiber is removed at 130℃ for 3 hours, and the subsequent premixing and extrusion parameters are set according to high standards. Test method: The test process is consistent with the experimental group, the sample is processed, and the mass loss rate is calculated after 1000 revolutions of friction on the Taber wear tester according to standard parameters, and the test is repeated 5 times.
[0039] Test data: The average mass loss rate is 0.14%. There are many medium-depth scratches on the surface. The areas with sparse distribution of ceramic micropowder at the micro level are severely worn. Although there are other ingredients in synergy, the wear resistance is not as good as the experimental group due to the small amount of ceramic micropowder and insufficient wear-resistant hard points. The specific results are as follows: Embodiment 2: Experimental Group Based on the experimental group of Example 1, the material formula and preparation are exactly the same as those of the experimental group of Example 1.
[0040] Test method: According to ASTMD6110-04 "Standard Test Method for Notched Impact Strength of Plastics", the pendulum impact tester was used for testing. The composite material was first injection molded into a notched specimen of standard size (80mm long, 10mm wide, and 4mm thick). The notch type was V-shaped, the notch depth was 2mm, and a gauge with an accuracy of 0.01mm was used to ensure the notch size accuracy. During the test, the specimen was placed horizontally on the fixture of the test machine, the starting angle of the pendulum was adjusted to 150°, and the pendulum was released to impact the midpoint of the back of the notch of the specimen in a free fall form. The pendulum energy was set to 5J. The test machine automatically records the force-displacement curve of the impact process, and the impact fracture energy is obtained by integrating the area under the curve to measure the toughness of the material. Ten specimens were tested in each group and the average value was taken to eliminate the influence of individual differences.
[0041] Test data: The average fracture energy reaches 8.8J. Fine silver streaks appear on the surface of the sample after impact. Although there is obvious deformation, it is not broken. The crack propagation is slow and is effectively blocked by the synergistic effect of the modified thermoplastic elastomer cross-linking network, polyurethane soft segment and nano-calcium carbonate, forming multiple energy dissipation mechanisms inside the material, showing excellent toughness.
[0042] Control group 1 Material formula: 55 parts of ultra-high molecular weight polyethylene, ceramic powder (Al 2 O 3 :ZrO 2=2:1) 20 parts, silane coupling agent 2 parts, polytetrafluoroethylene powder 3 parts, unmodified thermoplastic elastomer 55 parts, polyurethane 25 parts, nano calcium carbonate 10 parts, dioctyl phthalate 4 parts, hindered phenol antioxidant (antioxidant 3114) 1 part, glass fiber reinforced nylon 50 parts, glass fiber 20 parts, polyoxymethylene 10 parts, zinc stearate 1 part. That is, only the modified thermoplastic elastomer is replaced with an ordinary unmodified product, and the remaining ingredients are set according to the minimum value or similar to the corresponding claim 1. The preparation process has no modification step, and the other experimental groups are similar.
[0043] Preparation method: After ultra-high molecular weight polyethylene is dried at 80°C for 4 hours and at 100°C for 3 hours, ceramic micropowder is processed according to the process and silane coupling agent is added to obtain the outer layer material; unmodified thermoplastic elastomer and polyurethane and other components are stirred at 800r / min for 20 minutes and heated at 80°C to obtain the middle layer; glass fiber is treated at 120°C for 2 hours to remove impurities and pre-mixed with other inner layer components to extrude the inner layer; the three layers are injection molded.
[0044] Test method: Same as the test method of the experimental group, prepare standard notched specimens, and use a pendulum impact tester with a pendulum starting angle of 150° and a pendulum energy of 5J to impact, and measure 10 specimens to obtain the average fracture energy.
[0045] Test data: The average fracture energy is only 4.0J. The sample breaks quickly during impact and the crack runs through the sample. Due to the lack of fine structures such as cross-linking reinforcement of modified thermoplastic elastomers and synergistic toughening of nanoparticles, it is unable to effectively dissipate energy and prevent crack initiation and expansion, and the toughness is much lower than that of the experimental group.
[0046] Control group 2 Material formula: 65 parts of ultra-high molecular weight polyethylene, ceramic powder (Al 2 O 3 :ZrO 2 =2:1) 30 parts, silane coupling agent 3 parts, polytetrafluoroethylene powder 5 parts, modified thermoplastic elastomer 55 parts, polyurethane 35 parts, nano calcium carbonate 5 parts, dioctyl phthalate 6 parts, hindered phenol antioxidant (antioxidant 3114) 2 parts, glass fiber reinforced nylon 60 parts, glass fiber 30 parts, polyoxymethylene 15 parts, zinc stearate 2 parts. Maintain the experimental group settings of most components, only nano calcium carbonate is adjusted to the minimum value of 5 parts.
[0047] Preparation method: Each component is prepared according to the corresponding proportion, and the ultra-high molecular weight polyethylene is dried at 90°C for 6 hours and treated with ceramic micropowder to prepare the outer layer; the modified thermoplastic elastomer is used as the main middle layer, stirred at 1000r / min for 30 minutes and heated at 90°C; the glass fiber is treated at 130°C for 3 hours to remove impurities and then pre-mixed and extruded with the inner layer components; three-layer injection molding.
[0048] Test method: Prepare the specimens according to the experimental group standard, test them under the same conditions on a pendulum impact tester, and record the impact fracture energy of 10 specimens to calculate the average value.
[0049] Test data: The average fracture energy is 7.0J. More silver streaks are produced under impact and the crack extension is faster than that of the experimental group. Due to the small amount of nano calcium carbonate, it is difficult to give full play to the nano effect to build an efficient energy dissipation and crack blocking system. The toughness is weaker than that of the experimental group. The specific results are as follows: Embodiment 3: Experimental Group Material formulation and preparation: 60 parts of ultra-high molecular weight polyethylene, 25 parts of ceramic micropowder, 2.5 parts of silane coupling agent, 4 parts of polytetrafluoroethylene micropowder, 50 parts of modified thermoplastic elastomer, 30 parts of polyurethane, 12 parts of nano calcium carbonate, 5 parts of dioctyl phthalate, 1.5 parts of hindered phenol antioxidant, 55 parts of glass fiber reinforced nylon, 25 parts of glass fiber, 12 parts of polyoxymethylene, and 1.5 parts of zinc stearate. The modified thermoplastic elastomer is prepared according to steps A1-A5: in step A1, the thermoplastic elastomer and polybutylene terephthalate are accurately weighed at a ratio of 80:20 and dried in a vacuum oven at 80°C for 5 hours; in step A2, the thermoplastic elastomer is operated in a co-rotating twin-screw extruder, the starting temperature of zone 1 is set to 180°C, the dried thermoplastic elastomer is put in, and after it is initially melted (the screw speed is stably controlled at 300r / min), polybutylene terephthalate is added, and as the material moves forward, zone 2 is heated. The temperature was raised to 200°C, the third zone reached 210°C, and the fourth zone reached 220°C. After sufficient mixing, the mixture was extruded from the die, cooled and pelletized to obtain a primary modified product. In the A3 stage, nano-silicon dioxide with a particle size of 20-50nm was selected, and the mixture was placed in an ultrasonic dispersion device (400-600W power) with anhydrous ethanol solution at a mass ratio of 10:1 for 40 minutes to form a uniform suspension. KH-550 accounting for 3% to 5% of the mass of nano-silicon dioxide was added dropwise, and the mixture was heated to 400°C and 200°C. The mixture was heated to 200°C and 200°C. The mixture was cooled and pelletized to obtain a primary modified product. In the A3 stage, nano-silicon dioxide with a particle size of 20-50nm was selected, and the mixture was placed in an ultrasonic dispersion device (400-600W power) with anhydrous ethanol solution at a mass ratio of 10:1 to form a uniform suspension. KH-550 accounting for 3% to 5% of the mass of nano-silicon dioxide was added dropwise, and the mixture was heated to 60-70°C in an oil bath. Stir the reaction at 300-400r / min; A4 process, weigh the primary modified thermoplastic elastomer and nano-silicon dioxide at a ratio of 95:5, put them into a high-speed mixer and premix them at 600-800r / min for 18 minutes, then put them into a twin-screw extruder (the temperature zones are 190°C in zone 1, 210°C in zone 2, 220°C in zone 3, 230°C in zone 4, and 230°C in zone 5, and the screw speed is 400r / min), and the secondary modified material is produced after cooling and pelletizing; A 5 procedure, with the secondary modified thermoplastic elastomer as the matrix, dicumyl peroxide and triallyl isocyanurate were accurately weighed at a mass ratio of 0.5% and 1%, respectively, and the mixture was first placed in a high-speed mixer (speed 200-300r / min) and stirred for 12 minutes, and then the two were added in sequence to obtain the mixture, which was put into an internal mixer preheated to 170°C (after the material is added, the speed is 30-40r / min) for internal mixing for 12 minutes to successfully obtain a three-dimensional cross-linked network structure modified thermoplastic elastomer.
[0050] The overall preparation process follows the B1-B4 specifications: In step B1, the ultra-high molecular weight polyethylene particles are dried in a vacuum oven at 85°C for 5 hours, mixed with ceramic micropowder dried at 105°C for 4 hours, stirred at high speed (speed 900r / min), and then added with a corresponding amount of silane coupling agent, processed by a twin-screw extruder (the temperature of each area is finely set according to the process to ensure uniform plasticization and smooth extrusion of the material), and then cooled in a water tank, blown dry, and pelletized to obtain the outer wear-resistant layer material; in step B2, the modified thermoplastic elastomer, polyurethane and other ingredients are put into the mixer in sequence, stirred at a speed of 900r / min and heated to 85°C, and stirred for 25 minutes to fully merge to form the middle toughening layer material; in operation B3, the glass fiber is heated at 125 ℃ oven for impurity removal for 2.5 hours, soaked in a diluted solution of silane coupling agent and water in a mass ratio of 1:10 and then dried, and put into a mixer for premixing with glass fiber reinforced nylon, treated glass fiber, polyoxymethylene, and zinc stearate in turn (premixing speed 700r / min, duration 12 minutes), and then extruded through a twin-screw extruder (the temperature of each area is accurately set according to the inner layer process) to form an inner support layer material; in the B4 stage, the outer wear-resistant layer, the middle toughening layer, and the inner support layer materials are injected into the mold in sequence by means of an injection molding machine (the injection molding parameters are finely adjusted according to the mold characteristics and material flow characteristics, covering injection pressure, speed, holding time and other aspects), cooled and demolded, and finally a high-toughness and wear-resistant badminton composite material is made.
[0051] Test methods and data: Wear resistance test: The test work was carried out in accordance with the national standard "Measurement Method for Wear Resistance of Plastics". The prepared composite material was carefully processed into a circular specimen with a diameter of 50mm and a thickness of 5mm in advance, and the surface of the specimen was carefully cleaned and polished to ensure that it was smooth, flawless and isotropic. During the test, a 5N weight was firmly loaded on the surface of the specimen, and an H-18 grinding wheel was selected as the friction medium. The speed of the Taber wear tester was set to 7200r / min, so that the grinding wheel was in close contact with the surface of the specimen and continued to rub for 1000 revolutions. After the friction test was completed, an electronic balance with an accuracy of 0.0001g was used to accurately weigh the mass of the specimen before and after friction. The mass loss rate was scientifically calculated based on the mass difference. After 5 repeated tests, the average value was taken as the final result. After measurement, the average mass loss rate was 0.08%, which fully demonstrated the excellent wear resistance of the material. Only slight scratches remained on the surface of the specimen. The material structure at the microscopic level was stable, and the wear-resistant particles and reinforcing fibers did not fall off or shift.
[0052] Toughness performance test: The test was carried out in strict accordance with ASTMD6110-04 "Standard Test Method for Notched Impact Strength of Plastics". Initially, the composite material was molded into a standard size (80mm long, 10mm wide, 4mm thick) specimen with a V-notch (notch depth 2mm) by injection molding, and the notch size accuracy was strictly controlled using a measuring tool with an accuracy of 0.01mm. During the test, the specimen was placed horizontally on the fixture of the pendulum impact tester, and the starting angle of the pendulum was accurately adjusted to 150°. The pendulum was released to impact the midpoint of the back of the specimen notch in a free fall posture, and the pendulum energy was preset to 5J. The test machine automatically records the force-displacement curve of the entire impact process, and uses the integral calculation of the area under the curve to accurately obtain the impact fracture energy. Each group tested 10 specimens and the average value was obtained, successfully eliminating the interference of individual differences. The average fracture energy measured reached 8.5J. Although the specimen was deformed after the impact, it did not break. The crack was blocked by the modified structure inside the material and expanded slowly, highlighting the excellent toughness of the material.
[0053] Test the material density by the drainage method, weigh the mass of the clean and dry empty specific gravity bottle, and record it as Then fill the pycnometer with distilled water and place it in a constant temperature water bath for 30 minutes. Then use filter paper to carefully wipe off the water attached to the outside of the bottle and weigh the mass again, which is recorded as , accurately weigh a certain mass and record it as The composite material sample to be tested is carefully placed in the specific gravity bottle, then filled with distilled water, and after carefully eliminating bubbles, it is returned to the constant temperature water bath for 30 minutes. After taking it out and wiping the water outside the bottle with filter paper, the mass is weighed. , according to the formula ,in, Calculate the density of the material from the density of distilled water at the test temperature.
[0054] Preparation size is long ,Width ,high The sample was placed in a high temperature and high humidity environment box for 72 hours. After it was taken out and cooled to room temperature, the length was accurately measured again using a measuring tool with an accuracy of 0.01mm. ,Width ,high According to the formula: Calculate dimensional stability.
[0055] Control group 1 Material formula and preparation: The material formula was maintained consistent with that of the experimental group, but adjustments were made in the preparation process. In the preparation of the intermediate layer in step B2, the mixer speed was reduced to 400r / min, the heating temperature was reduced to 70°C, and the stirring time was shortened to 15 minutes. The remaining process parameters such as raw material processing, extrusion of each layer of materials, and injection molding were all executed according to the corresponding process of the experimental group, and only adaptive changes were made based on the above adjustments.
[0056] Test methods and data: The comprehensive performance of the material was evaluated using the same test method as the experimental group. After the wear resistance test (following the "Plastic Wear Resistance Determination Method", the same sample specifications and test conditions), the average mass loss rate was 0.12%, which was higher than that of the experimental group. The number of scratches on the sample surface increased and the depth increased slightly. It can be seen at the microscopic level that some components are not well fused, and the uniformity of the wear-resistant phase distribution is affected; the toughness performance test (according to the ASTMD6110-04 standard, the same sample preparation and test settings) obtained an average fracture energy of 7.2J, which is lower than that of the experimental group. The crack propagation speed during impact is accelerated, and the internal energy dissipation efficiency of the material is reduced. Due to insufficient stirring and inadequate heating of the middle layer, the synergistic toughening effect of the components is discounted; the material density test (drainage method, step flow, and accuracy requirements are the same as the experimental group) measured a value of 1.30g / cm³, which is different from the experimental group, suggesting that the tightness of the internal structure has changed; the dimensional stability test (same environmental conditions, measurement process) results show that the dimensional change rate is large, exceeding the experimental group, indicating that under the test of temperature and humidity environment, the stability of the material structure has deteriorated and it is difficult to maintain precise dimensions.
[0057] Control group 2 Material formula and preparation: The material formula remains the same as the experimental group, but adjustments are made in the injection molding stage of step B4 of the preparation process. The injection temperature is reduced by 20°C, and the injection speed is increased by 20%. The mold cooling process is not standardized, and the cooling time is deliberately shortened. For the process parameters of the other links such as the preliminary processing of raw materials and the preparation of materials for each layer, the original settings of the experimental group are maintained, and only adjustments are made in the injection molding step to adapt to the above changes.
[0058] Test methods and data: The material properties were evaluated according to the unified test method of the experimental group. The wear resistance test showed that the average mass loss rate climbed to 0.16%, the specimens showed serious wear marks, the microstructure was loose, and the risk of wear-resistant phase shedding increased; the average fracture energy of the toughness test was only 6.8J, the material was quickly destroyed under impact, and the cracks penetrated out of control, which was caused by the out-of-control injection molding process, resulting in uneven stress distribution inside the material, the destruction of interlayer bonding, and the inability to exert synergistic toughening; the material density test value was 1.35g / cm³, which deviated from the reasonable range, reflecting the increase in internal micro defects; the dimensional change rate of the dimensional stability test deteriorated to, which seriously exceeded the experimental group, which means that it is difficult for the material to ensure a stable appearance and structure under actual working conditions, and the comprehensive performance has declined significantly. The specific results are as follows: Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. A high-toughness wear-resistant badminton composite material, characterized in that: include: 55-65 parts of ultra-high molecular weight polyethylene, 20-30 parts of ceramic powder, 2-3 parts of silane coupling agent, 3-5 parts of polytetrafluoroethylene powder, 45-55 parts of modified thermoplastic elastomer, 25-35 parts of polyurethane, 10-15 parts of nano calcium carbonate, 4-6 parts of dioctyl phthalate, 1-2 parts of hindered phenol antioxidant, 50-60 parts of glass fiber reinforced nylon, 20-30 parts of glass fiber, 10-15 parts of polyoxymethylene and 1-2 parts of zinc stearate, wherein the preparation method of the modified thermoplastic elastomer is as follows: Step A1: weighing the thermoplastic elastomer and polybutylene terephthalate in a mass ratio of 80:20, placing them in a vacuum oven, and drying them at 80° C. for 4-6 hours; Step A2: setting the temperature to 180° C., firstly adding the dried thermoplastic elastomer into a vacuum oven through a co-rotating twin-screw extruder, and after the dried thermoplastic elastomer is initially melted, adding polybutylene terephthalate, blending through a screw extruder, and then extruding through a die head, cooling in a water tank, drawing and pelletizing, to obtain a primary modified thermoplastic elastomer; Step A3: Add nano-silicon dioxide to the primary modified thermoplastic elastomer, disperse it using an ultrasonic dispersing device to obtain a uniform suspension, and then dropwise add , stirring after oil bath; Step A4: weighing the primary modified thermoplastic elastomer and nano-silicon dioxide in a mass ratio of 95:5, then putting them into a high-speed mixer for premixing, putting them into a twin-screw extruder, cooling and pelletizing to obtain a secondary modified thermoplastic elastomer; Step A5: Taking the secondary modified thermoplastic elastomer as a matrix, diisopropylbenzene oxide and triallyl isocyanurate are weighed in a mass ratio of 0.5%:1%, and the secondary modified thermoplastic elastomer is first placed in a high-speed mixer, and diisopropylbenzene oxide and triallyl isocyanurate are added in sequence during the stirring process to obtain a mixture, and the mixture is put into an internal mixer to obtain a modified thermoplastic elastomer.
2. The high-toughness and wear-resistant badminton composite material according to claim 1, characterized in that: The molecular weight of the ultra-high molecular weight polyethylene is greater than 1.5 million, the ceramic micropowder is a mixture of aluminum oxide and zirconium oxide, the silane coupling agent has a methoxy group at one end and an epoxy group at the other end, the polytetrafluoroethylene is a high molecular polymer prepared by polymerizing tetrafluoroethylene as a monomer, the polyurethane is a high molecular polymer generated by the reaction of polyols and isocyanates, the particle size of the nano calcium carbonate is between 1-100 nm, and the hindered phenol antioxidant is antioxidant 3114.
3. The high-toughness and wear-resistant badminton composite material according to claim 1, characterized in that: In step A2, the vacuum oven is divided into four zones, the temperature of zone 1 is set to 180°C, the screw speed is set to 300r / min, and during the blending process of the screw extruder, the materials are moved to subsequent zones, with the temperature of zone 2 being 200°C, the temperature of zone 3 being 210°C, and the temperature of zone 4 being 220°C.
4. The high-toughness and wear-resistant badminton composite material according to claim 1, characterized in that: In the step A3, the particle size of nano-silicon dioxide is 20-50 nm, and it is dispersed with anhydrous ethanol solution at a mass ratio of 10:1, the dispersing power of the ultrasonic dispersing equipment is 400W-600W, the dispersing time is 30-45min, and the silane coupling agent added dropwise The silica is KH-550, and the silane coupling agent accounts for 3% to 5% of the mass of the silica. The oil bath temperature is 60° C. to 70° C., and the stirring speed is 300 to 400 r / min.
5. The high-toughness and wear-resistant badminton composite material according to claim 1, characterized in that: In the step A4, the premixing time is 15 to 20 minutes, the premixing speed is 600-800 r / min, the twin-screw extruder is divided into five zones, the temperature of zone 1 is 190°C, the temperature of zone 2 is 210°C, the temperature of zone 3 is 220°C, the temperature of zone 4 is 230°C, the temperature of zone 5 is 230°C, and the screw speed is 400 r / min.
6. The high-toughness and wear-resistant badminton composite material according to claim 1, characterized in that: In the step A5, the secondary modified thermoplastic elastomer is placed in a high-speed mixer at a rotation speed of 200-300 r / min and a stirring time of 10-15 min. The internal mixer is preheated to 170° C. before the material enters. After the material enters, the rotation speed is 30-40 r / min and the internal mixing time is 10-15 min. The modified thermoplastic elastomer obtained has a three-dimensional cross-linked network structure.
7. A method for preparing a high-toughness wear-resistant badminton composite material, characterized in that: The following steps are involved: Step B1: placing ultra-high molecular weight polyethylene particles in a vacuum oven to dry, then adding ceramic micropowder, stirring at high speed, adding silane coupling agent, extruding, cooling in a water tank, drying, and pelletizing to obtain an outer wear-resistant layer material; Step B2: respectively putting the modified thermoplastic elastomer, polyurethane, nano calcium carbonate, dioctyl phthalate, and hindered phenol antioxidant into a mixer, stirring and heating to obtain a middle toughening layer material; Step B3: placing the glass fiber in an oven to remove impurities, then soaking it in a diluted silane coupling agent solution and drying it, adding glass fiber reinforced nylon, treated glass fiber, polyoxymethylene and zinc stearate to a mixer in sequence for premixing, and then extruding it to obtain an inner support layer material; Step B4: injecting the outer wear-resistant layer material, the middle toughening layer material and the inner support layer material into the mold through an injection molding machine, and after cooling and demolding, obtaining a high-toughness wear-resistant badminton composite material.
8. The method for preparing a high-toughness wear-resistant badminton composite material according to claim 7, characterized in that: In the step B1, the ultra-high molecular weight polyethylene particles are dried at 80-90° C. for 4-6 hours, the ceramic powder is mixed with alumina and zirconium oxide in a mass ratio of 2:1, and dried at 100-110° C. for 3-5 hours, and the amount of silane coupling agent added is 2% to 3% of the mass of the ceramic powder.
9. The method for preparing a high-toughness wear-resistant badminton composite material according to claim 7, characterized in that: In step B2, the speed of the stirrer is 800-1000 r / min, the time is 20-30 min, and the heating temperature is 80-90° C.
10. The method for preparing a high-toughness wear-resistant badminton composite material according to claim 7, characterized in that: In the step B3, the impurity removal temperature of the glass fiber is 120-130° C., the impurity removal time is 2-3 hours, and the silane coupling agent dilution solution is prepared by mixing the silane coupling agent and water in a mass ratio of 1:10.